Rapid urbanization and policy variation greatly drive ecological quality evolution in Guangdong-Hong Kong-Macau Greater Bay Area of China: A remote sensing perspective. (August 2020) - Yang, Chao; Zhang, Chenchen; Li, Qingquan; Liu, Huizeng; Gao, Wenxiu; Shi, Tiezhu; Liu, Xu; Wu, Guofeng
Highlights: The proposed comprehensive ecological evaluation index (CEEI) is an effective method in revealing ecological quality. Urbanization process and policy variation play dominant roles in ecological quality evolution. Poor and fair ecological quality areas shift from suburbs to urban areas gradually. Both positive and negative signals for ecological conservation were found in the GBA. Abstract: As one of the major bay areas in the world, the Guangdong-Hong Kong-Macau Greater Bay Area (GBA) has been experiencing a remarkable urbanization process, and its ecological quality also has been suffering from intense human activities and urbanization inevitably. This study aimed to reveal the spatiotemporal characteristics of ecological quality evolution under the pressure of urbanization in the GBA from 1987 to 2017. A comprehensive ecological evaluation index (CEEI) was proposed to describe the spatiotemporal characteristics change of ecological quality by integrating the remote sensing-based parameters of vegetative cover (VC), vegetative health index (VHI), normalized differential build-up and bare soil index (NDBSI), land surface moisture (LSM) and land surface temperature (LST). The results revealed that: (1) the evolution of ecological quality showed a trend of first improvement then degradation from 1987 to 2017 and the regions with poor and fair ecological quality gradually shifted from suburbs to urban areas; (2) the ecological quality was not optimistic in 1987, with the areas with poor and fair ecological quality reaching 3.45% and 30.36% of total area, respectively; (3) the ecological quality greatly improved in 1997 and 2007, and the areas with poor ecological quality only accounted for 0.41% and 0.70% of total area, respectively; and (4) the ecological quality degraded again in 2017, and the degraded area reached 52% and the areas with poor and fair ecological quality reached 4.3% and 17.35%, respectively. The changes of ecological quality were mainly driven by urbanization process and policy variation, and these results may provide helpful information for the ecological conservation and sustainable development of GBA.